In vitro and in vivo Assessment of Keratose as a Novel Excipient of Paclitaxel Coated Balloons - Turner, Emily; Erwin, Megan; Atigh, Marzieh; Christians, Uwe; Saul, Justin M.; Yazdani, Saami K. (Frontiers in Pharmacology, 2018)
Purpose: Drug coated balloons (DCB) are continually improving due to advances in coating techniques and more effective excipients. Paclitaxel, the current drug choice of DCB, is a microtubule-stabilizing chemotherapeutic agent that inhibits smooth muscle cell proliferation. Excipients work to promote coating stability and facilitate paclitaxel transfer and retention at the target lesion, although current excipients lack sustained, long-term paclitaxel retention. Keratose, a naturally derived protein, has exhibited unique properties allowing for tuned release of various therapeutic agents. However, little is known regarding its ability to support delivery of anti-proliferative agents such as paclitaxel. The goal of this project was to thus demonstrate the feasibility of keratose as a DCB-coating excipient to promote the release and delivery of paclitaxel. Methods: Keratose was combined with paclitaxel in vitro and the release kinetics of paclitaxel and keratose were evaluated through high performance liquid chromatograph-mass spectroscopy (HPLC-MS) and spectrophotometry, respectively. A custom coating method was developed to deposit keratose and paclitaxel on commercially available angioplasty balloons via an air spraying method. Coatings were then visualized under scanning electron microscopy and drug load quantified by HPLC-MS. Acute arterial transfer of paclitaxel at 1 hour was assessed using a novel ex vivo model and further evaluated in vivo in a porcine ilio-femoral injury model. Results: Keratose demonstrated tunable release of paclitaxel as a function of keratose concentration in vitro. DCB coated via air spraying yielded consistent drug loading of 4.0±0.70 µg/mm2. Under scanning electron microscopy, the keratose-paclitaxel DCB showed uniform coverage with a consistent, textured appearance. The acute drug transfer of the keratose-paclitaxel DCB was 43.60±14.8 ng/mg at 1 hour ex vivo. These measurements were further confirmed in vivo as the acute 1 hour arterial paclitaxel levels were 56.60±66.4 ng/mg. Conclusions: The keratose-paclitaxel coated DCB exhibited paclitaxel uptake and achieved acute therapeutic arterial tissue levels, confirming the feasibility of keratose as a novel excipient for DCB.